Potential of enhancer of zeste homolog 2 inhibitors for the treatment of SWI/SNF mutant cancers and tumor microenvironment modulation. Issue 6 (9th February 2021) - Pyziak, Karolina; Sroka‐Porada, Agnieszka; Rzymski, Tomasz; Dulak, Józef; Łoboda, Agnieszka
Abstract: Enhancer of zeste homolog 2 (EZH2), a catalytic component of polycomb repressive complex 2 (PRC2), is commonly overexpressed or mutated in many cancer types, both of hematological and solid nature. Till now, plenty of EZH2 small molecule inhibitors have been developed and some of them have already been tested in clinical trials. Most of these inhibitors, however, are effective only in limited cases in the context of EZH2 gain‐of‐function mutated tumors such as lymphomas. Other cancer types with aberrant EZH2 expression and function require alternative approaches for successful treatment. One possibility is to exploit synthetic lethal strategy, which is based on the phenomenon that concurrent loss of two genes is detrimental but the deletion of either of them leaves cell viable. In the context of EZH2/PRC2, the most promising synthetic lethal target seems to be SWItch/Sucrose Non‐Fermentable chromatin remodeling complex (SWI/SNF), which is known to counteract PRC2 functions. SWI/SNF is heavily involved in carcinogenesis and its subunits have been found mutated in approximately 20% of tumors of different kinds. In the current review, we summarize the existing knowledge of synthetic lethal relationships between EZH2/PRC2 and components of the SWI/SNF complex and discuss in detail the potential application of existing EZH2 inhibitors in cancer patients harboring mutations in SWI/SNF proteins. We also highlight recent discoveries of EZH2 involvement in tumor microenvironment regulation and consequences for future therapies. Although clinical studies are limited, the fundamental research might help to understand which patients are most likely to benefit from therapies using EZH2 inhibitors.